2015
DOI: 10.1111/dmcn.12830
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and behavioural problems in young children with autism spectrum disorder

Abstract: AIM To assess the frequency, pervasiveness, associated features, and persistence of emotional and behavioural problems in a community sample of young children with autism spectrum disorder (ASD).METHOD Parents (n=277) and teachers (n=228) of 4-to 8-year-olds completed the Developmental Behaviour Checklist (DBC). Intellectual ability and autism symptomatology were also assessed. A subsample repeated the DBC.RESULTS Three-quarters of the cohort scored above the clinical cut-off on the Developmental Behaviour Che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 23 publications
(40 reference statements)
3
63
2
2
Order By: Relevance
“…Clinicians must actively ask about signs and symptoms of these conditions, although management is generally similar to that for children without ASD. Co-occurring mental health conditions, such as anxiety and depression,221222223 and behavioral disorders such as ADHD,224225 also have important effects on health related quality of life 226. Here again, clinicians should specifically ask about symptoms of co-occurring mental health conditions and behavioral disorders, recognizing that specialized assessment, which takes into account communication challenges and symptom overlap, may be needed.…”
Section: Assessment Does Not End At Diagnosis: Asd Symptom Trajectoriesmentioning
confidence: 99%
“…Clinicians must actively ask about signs and symptoms of these conditions, although management is generally similar to that for children without ASD. Co-occurring mental health conditions, such as anxiety and depression,221222223 and behavioral disorders such as ADHD,224225 also have important effects on health related quality of life 226. Here again, clinicians should specifically ask about symptoms of co-occurring mental health conditions and behavioral disorders, recognizing that specialized assessment, which takes into account communication challenges and symptom overlap, may be needed.…”
Section: Assessment Does Not End At Diagnosis: Asd Symptom Trajectoriesmentioning
confidence: 99%
“…Salazar et al (2015) reported that in a group of 101 children diagnosed with ASD at age 5–9 over 90% had at least one comorbid psychiatric disorder. Another recent study found that in a community sample of children with ASD aged 4–8 years old three-quarters had parent-reported emotional/behavioral problems, while two-thirds of these children who parents reported as being above the clinical cut-off for emotional/behavioral problems also had teacher-reported problems, as assessed by the Developmental Behavior Checklist (DBC; Einfeld and Tonge 2002) (Chandler et al 2016). Preschool children with ASD as young as 2–4 years old have also been found to have increased levels of emotional/behavioral symptoms as assessed by the Child Behavior Checklist (CBCL; Achenbach and Rescorla 2000) (Georgiades et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Atypical or impaired ER has been implicated in the development and maintenance of most, if not all, psychiatric disorders (Berking & Wupperman, 2012). Yet, ER has been relatively neglected in ASD research until recently, which is surprising given the prominence of aberrant emotional functioning for so many individuals with ASD (e.g., Chandler et al, 2015). …”
mentioning
confidence: 99%